Account Receivables, Payables Management, and Financial Performance of Public Universities in Kenya's Coastal Region - Ombui, Justin; Monari, Damaris; Kamau, Charles; Kibiti, Cromwell; Muhoro, Grieveson (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Kenyan public universities face significant challenges, including budget cuts that worsen their financial difficulties, declining enrollment due to the increase in number of universities, and higher expectations for quality education. The main purpose of this study was to assess how receivables accounts and payables management affect the financial performance of public universities in Kenya's coastal region. This research is based on the Cash Conversion Cycle theory. The primary data was collected by consulting financial controllers and other managers from selected public universities in the coastal region. The collected data was analyzed using descriptive and inferential methods of Pearson correlation and regression analyses. The results showed that effective working capital management practices have a positive and significant impact on financial performance, as confirmed by statistical analysis. Specifically, managing receivables and payables improves financial performance, while the size of the university influences the relationship between working capital management and financial outcomes. These findings highlight the importance of implementing appropriate financial management strategies that fit the specific needs and size of each institution. The study recommends prioritizing the development of strong cash management policies, improving receivables and payables management practices, optimizing inventory management strategies, and considering the impact of university size when designing working capital management approaches. Furthermore, the study emphasizes the need for further research to explore the long-term effects of these management practices and investigate the effectiveness of different strategies in enhancing financial sustainability and resilience in Kenyan public universities.
Keywords: Public Universities, Financial Performance, Receivables Management, Payables Management